Structural diversity and magnetic properties of four Cu(II)/Co(II) coordination complexes based on 3, 5-bis(2-carboxylphenoxy)benzoic acid. (15th February 2018) - Fan, Liming; Gao, Lingling; Wang, Xiaoqing; Wang, Jiang; Zhao, Li; Fang, Kegong; Hu, Tuoping
Graphical abstract: Four Cu(II)/Co(II) coordination complexes based on 3, 5-bis(2-carboxylphenoxy)benzoic acid with antiferromagnetic or spin transition behaviors. Abstract: Four coordination complexes, namely, [Cu(HBCB)] n (1 ), {[Cu(HBCB)( o -bimb)]·H2 O} (2 ), {[Cu1.5 (BCB)( m -bimb)1.5 ]·DMF} n (3 ), and [Co1.5 (BCB)(bpy)1.5 (H2 O)] n (4 ), have been assembled from the semirigid tripodal 3, 5-bis(2-carboxylphenoxy)benzoic acid (H3 BCB) in the presence or absence of the N-donors ( o -bimb = 1, 2-bis(imidazol-1-ylmethyl)benzene, m -bimb = 1, 3-bis(imidazol-1-ylmethyl)benzene, bpy = 4, 4′-bipyridine). Structural analyses revealed that complex1 features a {Cu2 (COO)4 } SBUs based 3D (3, 6)-connected {4·6 2 }2 {4 2 ·6 10 ·8 3 }-rtl net. Complex2 displays an interesting coordination molecule cage structure. Complex3 exhibits a 2D (3, 4, 4)-connected {4·6 2 }2 {4·6 4 ·8}2 {6 4 ·8 2 } sheet. And complex4 shows a 3D (3, 4, 6)-connected {5·6 2 }2 {5 6 ·6 4 ·7·8 2 ·9 2 }{6 4 ·8·9} net based on the binuclear {Co2 (COO)2 } SBUs and Co2 ions. The temperature-dependent magnetic susceptibilities indicated there are gradual spin transition behavior in1, and antiferromagnetic interactions in4 .